2013
DOI: 10.1111/j.1365-4632.2012.05584.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular aspects of psoriasis: an updated review

Abstract: Psoriasis, a systemic inflammatory disease, is associated with enhanced atherosclerosis and risk of cardiovascular (CV) disease, which may account for higher morbidity and mortality rates in psoriatic patients. It especially applies to younger psoriatic patients with more severe disease, reducing their life expectancy. The aim of the study was to review the literature on CV disease in psoriasis as well as the pathogenic mechanisms shared between psoriasis and atherosclerosis. Moreover, case-control and cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 80 publications
(198 reference statements)
1
51
2
2
Order By: Relevance
“…They suggested that the treatment of the inflammatory processes involved in the pathogenesis of both psoriasis and atherosclerosis may be beneficial in reducing the CV risk in psoriatic patients. [54] Indian Journal of Dermatology, Venereology, and Leprology | 2013 | Vol 79 | Supplement 1 S16…”
Section: Comorbidities and Management Of Psoriasismentioning
confidence: 98%
“…They suggested that the treatment of the inflammatory processes involved in the pathogenesis of both psoriasis and atherosclerosis may be beneficial in reducing the CV risk in psoriatic patients. [54] Indian Journal of Dermatology, Venereology, and Leprology | 2013 | Vol 79 | Supplement 1 S16…”
Section: Comorbidities and Management Of Psoriasismentioning
confidence: 98%
“…Past studies in rheumatoid arthritis have shown that systemic immune inhibitors can prevent atherosclerosis and lower the risk for cardiovascular disease (Pietrzak et al, 2013). For instance, tumor necrosis factor blockers, including infliximab, etanercept, and adalimumab, have been found to delay the first cardiovascular event and reduce the incidence of myocardial infarction and cardiovascular-related mortality in rheumatoid arthritis patients (Jacobsson et al, 2005;Dixon et al, 2007;Kerekes et al, 2009).…”
mentioning
confidence: 97%
“…The expression of thrombospondin-1, which is involved in the formation of atherosclerotic lesions (Moura et al, 2008), was decreased by 1.56-fold (Po0.05), and genes related to atherosclerosis disease risks and platelet aggregation (e.g., F2RL2) were also suppressed. Cardiovascular disease is one of the most prevalent comorbidities associated with psoriasis (Mehta et al, 2010) and contributes substantially to the morbidity and mortality rates in psoriatic patients (Pietrzak et al, 2013). Recent studies have indicated that IL-17 may be associated with the development of cardiovascular disease and atherosclerosis (Ding et al, 2011;Madhur et al, 2011).…”
mentioning
confidence: 99%
“…A recent meta-analysis indicates elevated risk of cardiovascular events in psoriatic patients in relation to non-psoriatic controls [9]. Also, Asian-Indians have a higher predisposition to obesity, metabolic syndrome, diabetes, and cardiovascular disorders as compared to western populations.…”
Section: Discussionmentioning
confidence: 99%